MASALAH GUGATAN PEMBATALAN PERKAWINAN YANG DIAJUKAN MELEWATI JANGKA WAKTI (PUTUSAN NOMOR 3617/PDT.G/2021/PA.DPK): The Problem Of Marriage Annulment Lawsuit Filed Past The Time Period (Decision Number 3617/Pdt.G/2021/Pa.Dpk - Ratu Salsabila Khairunnisa; Ning Adiasih (Faculty of Law, Universitas Trisakti, 2025)
One of the matters regulated in the Marriage Law is marriage annulment. Article 27 paragraph (3) of the Marriage Law stipulates that a lawsuit for annulment must be filed within six months after the marriage takes place. However, in the case of Decision Number 3617/Pdt.G/2021/PA.Dpk, the annulment lawsuit was filed after the specified period had passed and the judge approved the annulment of the marriage after 22 months of marriage. The problem examined is how the legal considerations of the judge who granted the marriage cancellation lawsuit filed exceeded the period. The results and conclusion showed that, referring to the provisions of Article 27 paragraph (3) of the Marriage Law and Article 72 Paragraph (3) of the Compilation of Islamic Law, the lawsuit should not be accepted because it has passed the stipulated period. The conclusion is that a marriage annulment filed after the six months should be considered unacceptable and the marriage remains legally valid.